Digital Business Transformation: Risks and Prospects ("Journal "U". Economy. Management. Finance.", 2020)
This article discusses the development of business in the digital direction. The digital transition began long before the coronavirus, but the pandemic has accelerated this process, in its most diverse directions and scales. Like any other change, there are good sides and bad sides. Digitalization of business has faced such problems as: cybercrime and cybercrime. These tasks can be prevented by digital compliance, which should create an auxiliary control system for the enterprise.
Keywords: business transformation; cybercrime; business process; digital compliance; blockchain